Verbal Aggressiveness in Communication in Media and Online. A Case Study of the TV Cooking Show »Spread« - Svobodova, Jindřiška; Nováková, Eva (Bohemistyka, 2019)
The paper discusses verbal aggressiveness and (im)politeness in media and online communication. The analysis focuses on transcriptions of communicative acts by participants of the TV reality Spread! ("Prostřeno!", a Czech version of the programme Come Dine with me) and viewers' comments in related online discussions. The analysis indicated that the use of face-threatening acts was determined by a type of communicative interaction and interlocutors' social roles. Striving to construct a positive self-image, the participants in the show did not take the risk of losing their face due to usage of derogatory or vulgar expressions in face-to-face inter- actions. The anonymous online discussions, on the contrary, did not pose any risk for the positive faces of the speakers; therefore, the interlocutors showed clear tendency to either appreciate and support, or attack the contestants as well as other speakers.